Risk Factors for Glaucoma Suspicion in Healthy Young Asian and Caucasian Americans - E. Lauren Doss; Linden Doss; Ying Han; Susan Huang; Travis Porco; Melike Pekmezci; Shan Lin (Journal of Ophthalmology)
Purpose. To determine the prevalence of certain risk factors for glaucoma in a healthy, young population and to compare these risk factors between Asian Americans and Caucasians. Methods. 120 healthy graduate students (mean age 24.8±3.0 years) underwent a comprehensive ophthalmic examination. Regression analyses controlling for age, sex, and refraction, comparing glaucoma risk factors in Asians (n=54) and Caucasians (n=41), were performed. Outcome variables included family history, intraocular pressure (IOP), spherical equivalent, central corneal thickness (CCT), mean deviation (MD) and pattern standard deviation (PSD), and disc and retinal nerve fiber layer (RNFL) parameters. Results. 61% of subjects were female; the mean spherical equivalent was -3.81±3.2 D; and the mean axial length (AL) was 25.1±1.7 mm. Regression analysis showed race affected spherical equivalent (P<0.001), AL (P=0.0073), IOP (P<0.001), and cup to disc area ratio (CDAR) (P=0.012). Family history, CCT, MD, and PSD did not vary between Asians and Caucasians (P>0.05). In this study, we found Asian Americans, compared to Caucasians, had 2.95±0.64 D greater myopia; greater IOP by 2.74±0.62 mmHg; and larger CDAR by 0.12±0.046. Conclusions. In our study population, young, healthy Asian Americans had greater myopia, IOP, and CDAR as compared to Caucasians, suggesting that racial variations can be important when diagnosing glaucoma.